The Influence of New Technologies on Tourism Consumption Behavior of the Millennials - Andreea Fortuna Șchiopu; Ana Mihaela Pădurean; Mădălina Lavinia Țală; Ana-Maria Nica (Amfiteatru Economic Journal, 2016)
The advent of new technologies has generated a series of mutations in the dynamics and structure of production and consumption at both global and tourism destinations level, increasing competition manifested on the tourist market, prompting efforts (concerns) from tourism service providers to diversify their offer, on the one hand, and to understand and investigate the needs, changing requirements of consumers (tourists), on the other hand. Studies of international tourist flows indicate that Millennials, also named the Y Generation - young people between 18 and 30 years old - will be the most dynamic component of the tourism market in the next decade. This article aims to analyze how new technologies influence the tourism consumption behavior of the members of the Millennials generation in Romania. Thus, a quantitative research, a survey, was conducted based on a questionnaire that had as objective the identification of electronic equipment, the applications, the ICT sources used by young people in the stages of planning, booking and development of the journey. The hypotheses tested the link between the importance given to technological resources and the extent to which young tourists are willing to share travel experiences later. Results of the research led to the development of a set of suggestions for key players in the tourism market.
Keywords: L83; M31; M37; 330; Millennials; generation Y; youth tourism; tourism consumption